Why Are Most Funds Open-End? Competition and the Limits of Arbitrage* - Stein, Jeremy C. (Quarterly Journal of Economics, 2005)
The majority of asset-management intermediaries (e.g., mutual funds, hedge funds) are structured on an open-end basis, even though it appears that the open-end form can be a serious impediment to arbitrage. I argue that the equilibrium degree of open-ending in an economy can be excessive from the point of view of investors. When funds compete for investors' dollars, they may engage in a counterproductive race towards the open-end form, even though this form leaves them ill-suited to undertaking certain types of arbitrage trades. One implication of the analysis is that, even absent short-sales constraints or other frictions, economically large mispricings can coexist with rational, competitive arbitrageurs who earn small excess returns.